Cross-Sectional and Longitudinal Effects of CREB1 Genotypes on Individual Differences in Memory and Executive Function: Findings from the BLSA - Wolf, Claudia; An, Yang; Tanaka, Toshiko; Bilgel, Murat; Gonzalez, Christopher; Kitner Triolo, Melissa; Resnick, Susan (Frontiers in Aging Neuroscience, 2017)
Abstract Purpose: Previously, we have shown that the SNP rs10932201 genotype of the cyclic AMP responsive element binding protein 1 gene (CREB1) contributes to individual differences in executive and memory function at the neural system and behavioral levels in healthy, young adults. However longitudinal effects of CREB1 genotypes on cognition have not yet been addressed. Furthermore we were interested in replicating associations between CREB1 genotypes and human cognition in previous cross-sectional studies and explore whether APOEε4 status might modify these relations. Methods: We investigated whether common, independent tag SNPs within CREB1 (rs2253206, rs10932201, rs6785) influence individual differences in age-related longitudinal change and level of executive function and memory performance independent of baseline age, sex, APOEε4 status and education. Our analysis included data from cognitively unimpaired older adults participating in the Baltimore Longitudinal Study of Aging (BLSA). Eleven measures from six cognitive tests (sample sizes range 617-786) were analyzed using linear mixed effects and generalized estimating equations models. Mean baseline age ranged from 50 to 69 years and mean time of follow-up (interval) ranged from 8 to 22 years. Results: We found significant effects of all three CREB1 SNPs on performance level and/or longitudinal change in performance based on eight measures assessing semantic memory, episodic memory, or both executive function and semantic memory. SNP rs10932201 showed the most significant and largest effect (Cohen’s d = -0.70, p < .01) on age-related longitudinal decline of semantic memory. Additionally, we show interactions between all three CREB1 SNPs and APOEε4 status on age-related longitudinal declines and levels of memory and executive function. Conclusions: Our results suggest that CREB1 genotypes independently and by interactions with APOEε4 status contribute to individual differences in cognitive aging.